2018
DOI: 10.1063/1.5008811
|View full text |Cite
|
Sign up to set email alerts
|

Direct variational determination of the two-electron reduced density matrix for doubly occupied-configuration-interaction wave functions: The influence of three-index N-representability conditions

Abstract: This work proposes the variational determination of two-electron reduced density matrices corresponding to the ground state of N-electron systems within the doubly occupied-configuration-interaction methodology. The P, Q, and G two-index N-representability conditions have been extended to the T1 and T2 (T2') three-index ones and the resulting optimization problem has been addressed using a standard semidefinite program. We report results obtained from the doubly occupied-configuration-interaction method, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…It has been recognized that the DOCI subspace captures most of the static correlations, serving as the first rung on a seniority ladder leading to the exact full configuration interaction (CI) solution. [34][35][36][37] The assumptions in DOCI drastically simplify the structure of the 2RDM 38,39 and reduce the scaling of the v2RDM method [40][41][42] while, expectedly, retain most of the correlation. Several applications of the v2RDM for seniority nonconserving Hamiltonians were already implemented and their accuracy tested against exact diagonalizations for small systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that the DOCI subspace captures most of the static correlations, serving as the first rung on a seniority ladder leading to the exact full configuration interaction (CI) solution. [34][35][36][37] The assumptions in DOCI drastically simplify the structure of the 2RDM 38,39 and reduce the scaling of the v2RDM method [40][41][42] while, expectedly, retain most of the correlation. Several applications of the v2RDM for seniority nonconserving Hamiltonians were already implemented and their accuracy tested against exact diagonalizations for small systems.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these basic conditions, more restrictive higher‐index N ‐representability conditions can be added. [ 26,27,30–33,35–37 ]…”
Section: Theorymentioning
confidence: 99%
“…The remainder of the 2‐RDM elements 2Dfalse˜jlik are zero. Moreover, the seniority number for DOCI wave functions is zero, and consequently, the expectation value of the corresponding seniority‐number operator trueΩ^ [ 31 ] is lefttrue〈〉normalΩfalse^DOCI=〈〉false∑σfalse∑iσaiσaiσfalse∑σfalse∑iσaiσaiσfalse¯aiσfalse¯aiσDOCI==N2false∑σiσ2trueD˜iσitrueσ¯iσitrueσ¯=0 …”
Section: Theorymentioning
confidence: 99%
“…The values arising from the 2-POS and (2,3)-POS v2RDM-DOCI procedures have been previously reported by us in Ref. 33; they have been included in this and other Tables in order to make an easier comparison with the results obtained from the method proposed in this work. As can be seen, in all cases, the full 3-POS conditions improve the energies from those using the 2-and (2,3)-POS by at least three and two orders of magnitude, respectively.…”
Section: B Molecular Systemsmentioning
confidence: 99%
“…Usually, the variational 2-RDM (v2RDM) calculations use a set of necessary N-representability constraints involving p-particle RDMs (p-RDM), known as p-positivity conditions. [28][29][30] In the DOCI space, recent calculations with molecular systems [31][32][33] and pairing models [34][35][36] have shown that the lower bounds on the ground-state energies obtained from v2RDM calculations converge rapidly with the number p of particles. Moreover, for attractive pairing interactions twopositivity conditions together with a subset of three-positivity conditions have shown to provide exact numerical results for a large variety of integrable models.…”
Section: Introductionmentioning
confidence: 99%